Secular trends and determinants of influenza vaccination uptake among patients with cardiovascular disease in Korea: Analysis using a nationwide database - Kim, Min; Yang, Bumhee; Gu, Seonhye; Kim, Eung-Gook; Kim, So Rae; Oh, Kyeong Seok; Yoon, Woong-Su; Bae, Dae-Hwan; Lee, Ju Hee; Kim, Sang Min; Choi, Woong Gil; Bae, Jang-Whan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Influenza vaccination reduces cardiovascular events in patients with cardiovascular disease (CVD). Identifying the factors that affect influenza vaccination uptake can help improve the prognosis in patients with CVD. This study aimed to evaluate the secular trends of influenza vaccination uptake and factors associated with lack of vaccination in individuals with CVD. Materials and methods We analyzed the annual trends and factors associated with influenza vaccination among 3,264 patients with CVD, included from the Korea National Health and Nutrition Examination Survey which reflect the health and nutritional status of the nationwide population of Korea conducted between 2007/2008 and 2018/2019. We used a stratified, multistage sampling method. Results The influenza vaccination rate was greater in patients with CVD (53–74%) than in those without CVD (28–40%). Multivariable logistic regression analysis showed that age <50 years [odds ratio (OR), 16.22; 95% confidence interval (CI), 7.72–34.07], 50–64 years (OR, 6.71; 95% CI, 4.37–10.28), male sex (OR, 1.45; 95% CI, 1.14–1.65), and asthma (OR, 0.45; 95% CI, 0.22–0.92) were independently associated with a lack of influenza vaccination. Among patients aged <65 years, smoking (OR, 2.30; 95% CI, 1.31–4.04), college graduation status (OR, 1.81; 95% CI, 1.16–2.82), and hypertension (OR, 0.70; 95% CI, 0.51–0.95) were independently associated with influenza vaccination. For individuals aged 65years, there was no significant determinant of lack of vaccination. Conclusion In patients with CVD, a continuous increase in the secular trend of influenza vaccination was demonstrated in Korea. Young age, male sex, and non-asthma status were independently associated with lack of influenza vaccination uptake.